Transcriptomic analysis of the mouse retina after acute and chronic normobaric and hypobaric hypoxia - L. J. A. Ebner (Nature Portfolio, 2021)
Abstract Oxygen delivery to the retinal pigment epithelium and the outer retina is essential for metabolism, function, and survival of photoreceptors. Chronically reduced oxygen supply leads to retinal pathologies in patients and causes age-dependent retinal degeneration in mice. Hypoxia can result from decreased levels of inspired oxygen (normobaric hypoxia) or reduced barometric pressure (hypobaric hypoxia). Since the response of retinal cells to chronic normobaric or hypobaric hypoxia is mostly unknown, we examined the effect of six hypoxic conditions on the retinal transcriptome and photoreceptor morphology. Mice were exposed to short- and long-term normobaric hypoxia at 400 m or hypobaric hypoxia at 3450 m above sea level. Longitudinal studies over 11 weeks in normobaric hypoxia revealed four classes of genes that adapted differentially to the hypoxic condition. Seventeen genes were specifically regulated in hypobaric hypoxia and may affect the structural integrity of the retina, resulting in the shortening of photoreceptor segment length detected in various hypoxic groups. This study shows that retinal cells have the capacity to adapt to long-term hypoxia and that consequences of hypobaric hypoxia differ from those of normobaric hypoxia. Our datasets can be used as references to validate and compare retinal disease models associated with hypoxia.